2011
DOI: 10.1021/jo200067y
|View full text |Cite
|
Sign up to set email alerts
|

Direct Arylation of Simple Azoles Catalyzed by 1,10-Phenanthroline Containing Palladium Complexes: An Investigation of C4 Arylation of Azoles and the Synthesis of Triarylated Azoles by Sequential Arylation

Abstract: Direct triarylation and sequential triarylation reactions of simple azoles catalyzed by [Pd(phen)(2)]PF(6) are described. Simple azoles, such as N-methylimidazole, thiazole, and oxazole, were observed to undergo triaryaltion reactions even at their C4 positions when treated with aryl iodides in the presence of [Pd(phen)(2)]PF(6) as a catalyst and a stoichiometric amount of Cs(2)CO(3) in DMA at 150 °C. Using excess amounts of azoles, selective C5 monoarylation was achieved by using the same catalytic system. Su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
38
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 127 publications
(40 citation statements)
references
References 97 publications
2
38
0
Order By: Relevance
“…16 Prior to our work, a single example of tristrifluoromethylphenylation of N-methylpyrazole in a moderate yield (52%) using [Pd(Phen) 2 ](PF 6 ) 2 catalyst was reported by Murai. 17 …”
Section: Resultsmentioning
confidence: 99%
“…16 Prior to our work, a single example of tristrifluoromethylphenylation of N-methylpyrazole in a moderate yield (52%) using [Pd(Phen) 2 ](PF 6 ) 2 catalyst was reported by Murai. 17 …”
Section: Resultsmentioning
confidence: 99%
“…Itami [89] found that a Pd II /bipy complex is effective for the C5-arylation of thiazoles, and finally Lee [119] found that Pd II /NHC ligand 85 is effective for the C5-selective arylation of imidazoles. [123] Scheme 17.24 Direct C-H arylation of 1,3-azoles with aryl halides, and applications of this methodology.…”
Section: C5-arylated 13-azolesmentioning
confidence: 99%
“…Subsequently, they accomplished the synthesis of Tie2 tyrosine kinase inhibitor 87 [122]. Murai and Shibahara [123] also synthesized this target via sequential C-H arylation from a simple imidazole using their robust catalyst, [Pd(phen) 2 ](PF 6 ) 2 . Sames [125] also reported multiple arylations of simple imidazoles using his own catalytic system.…”
Section: Application Of 13-azole C-h Arylation To Target-oriented Symentioning
confidence: 99%
“…Notwithstanding the importance of multiaryl‐substituted pyrazoles, direct CH arylation based on pyrazoles has attracted somewhat less attention. Recently, direct CH arylation at the C3‐, C4‐, and C5‐positions of pyrazoles8a, 17 and at the C3‐position of indazoles18 have been reported. In particular, Sames achieved a multiaryl‐substituted pyrazole synthesis starting from 4‐bromopyrazole with the aid of a 2‐(trimethylsilyl)ethoxymethyl (SEM) group 17c.…”
Section: Introductionmentioning
confidence: 99%